Determination of Judd-Ofelt parameters for Eu3+-doped alkali borate glasses. (December 2019) - Yu, Chunfeng; Zhang, Xizhen; Li, Xiangping; Zhang, Jinsu; Xu, Sai; Zhang, Xiangqing; Zhang, Yuhang; Wang, Xin; Wang, Li; Sui, Guozhu; Chen, Baojiu
Graphical abstract: Three sets of Judd-Ofelt parameters for Eu 3+ doped alkali borate glasses were derived, respectively, from absorption, excitation and emission spectra. It was found that these Judd-Ofelt parameters derived from different routes are fluctuated. The average values of the Judd-Ofelt parameters are suggested as the finally reliable values. The suggested values were examined by comparing the experimental fluorescence lifetimes with the calculated radiative transition lifetimes, and it was concluded that the suggested route for determining the Judd-Ofelt parameters is applicable. Highlights: J–O parameters of Eu 3+ were derived from absorption, emission and excitation spectrum. A route for achieving the reliable J–O parameters was proposed. The average values of J–O parameters were suggested to be used. The radiative transition properties of Eu 3+ were studied. Abstract: The radiative transition properties of Eu 3+ doped materials can hardly be quantitatively evaluated via traditional Judd-Ofelt (J–O) calculation procedure owing to the lack of available transitions in the absorption spectra. In this work, a new J–O calculation route was proposed and employed to Eu 3+ doped alkali borate glasses. Three sets of J–O parameters were obtained by using, respectively, the absorption, emission and excitation spectra, and the average J–O parameters involving more electric dipole transitions than in any individual spectrum were suggested to be used for quantificationally presenting radiative transition properties of Eu 3+ in the studied glasses. The radiative transition lifetime of 5 D0 level derived by using the J–O parameters was compared with the measured one, and good agreement was achieved. This fact indicated that the proposed J–O calculation route is practicable. Furthermore, the radiative transition rates and fluorescence branching ratios for Eu 3+ in the studied borate glasses were calculated.